Protosiphonorhinus patrickmuelleri gen. et sp. nov., the first fossil member of the sucking millipede family Siphonorhinidae (Colobognatha, Siphonophorida) described from Cretaceous Myanmar amber - Leif Moritz; Benjamin Wipfler; Thomas Wesener (Evolutionary Systematics)
Millipedes (Diplopoda) are an abundant group of fossilized terrestrial arthropods throughout the Palaeozoic Era. However, there is a gap in the Mesozoic Period with only slightly more than a dozen fossils known, until more recent fossil records – mainly from Cenozoic Dominican and Baltic ambers – became available. Here, we describe a millipede of the family Siphonorhinidae from Myanmar amber, a species-poor group, comprising just six extant genera, disjunctly distributed in Southeast Asia, South Africa, Madagascar, Chile and California. Micro-computed tomography (µ-CT) enabled detailed visualizations of essential elements for description, including the tergites, legs, head, antenna, and notably the gonopods. The new genus shares some characteristics with species of the extant genus Siphonorhinus Pocock, 1894. Protosiphonorhinus patrickmuelleri gen. et sp. nov. differs from extant species of the family mainly in the shape of the antenna, tergites, and anterior gonopods. A recently described fossil species of Siphonophorida from Myanmar amber was erroneously assigned to the family Siphonorhinidae. We transfer it to the family Siphonophoridae, as Siphonophora globosa (Su, Cai & Huang, 2024) comb. nov. The description of the new genus and the reinterpretation of the previously described fossil Siphonorhinidae allows for a rejection of a hypothesis of bradytely within the Siphonorhinidae from the mid-Cretaceous to the present day.